A gradient graphitized hard carbon material, preparation method and application thereof
By realizing gradient graphitization of the center and surface layers in hard carbon materials, and using layered nanooxide guiding agents, the problem of capacity limitation of traditional hard carbon materials in sodium-ion batteries is solved, and the sodium storage capacity and battery capacity are improved. chemical properties.
Patent Information
- Application Number
- CN202311173944.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-09-11
AI Technical Summary
Traditional hard carbon materials have capacity limitations in the embedding and deintercalation of sodium ions, which limits the further development of sodium ion batteries.
By controlling the degree of graphitization of hard carbon materials, gradient graphitization of the center and surface layers is achieved to increase sodium storage capacity, and the graphitization gradient of hard carbon materials is precisely controlled through the guiding agent of layered nanooxides.
The sodium storage capacity, first Coulombic efficiency and sample conductivity of hard carbon materials are improved, thereby comprehensively improving the electrochemical performance of sodium-ion batteries.
Smart Images

Figure CN117208890B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a gradient graphitized hard carbon material, a preparation method and application thereof. Background Art
[0002] As an energy storage technology, sodium-ion batteries have broad application prospects and have attracted much attention. The design and preparation of negative electrode materials play a vital role in the performance of sodium-ion batteries. Hard carbon materials have become the main choice of negative electrode materials for sodium-ion batteries due to their excellent electrochemical properties and low cost.
[0003] However, traditional hard carbon materials have capacity limitations during the insertion and deinsertion of sodium ions, which restricts the further development of sodium-ion batteries. In order to improve the sodium storage capacity of hard carbon materials, researchers have proposed many methods, such as using pore formers to increase the pore volume of hard carbon materials to obtain more sodium storage sites. However, most methods are either difficult to achieve large-scale production or sacrifice the first coulombic efficiency of the material. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a gradient graphitized hard carbon material with high sodium storage capacity, first coulomb efficiency and sample conductivity, and a preparation method and application thereof.
[0005] The present invention provides a hard carbon material, which comprises a central part and a surface layer; the graphitization degree of the hard carbon material gradually increases from the central part to the surface layer.
[0006] Preferably, the thickness ratio of the central portion to the surface layer is 1:0.1-1.2.
[0007] Preferably, the graphitization degree of the central portion ranges from 0% to 20%; and the graphitization degree of the surface layer ranges from 50% to 80%.
[0008] Preferably, the central portion and / or the surface layer are doped and dispersed with a high specific volume material; the high specific volume material is one or more of nano-silicon, nano-tin and nano-antimony.
[0009] Preferably, the central portion is coated with a high specific volume material to form a core-shell structure, and the high specific volume material is one or more of nano-silicon, nano-tin and nano-antimony.
[0010] Preferably, the D50 particle size of the hard carbon material is 2 to 20 μm;
[0011] And / or, the specific surface area of the hard carbon material is 2 to 1000 m 2 / g;
[0012] and / or, the average pore size of the hard carbon material is 1 to 50 nm;
[0013] And / or, the pore volume of the hard carbon material is 0.02 to 0.1 cm 3 / g.
[0014] Preferably, the powder resistance of the hard carbon material is 1 to 10 Ω·cm.
[0015] The present invention also provides a method for preparing a hard carbon material, comprising the following steps:
[0016] S1) impregnating the hard carbon material precursor in an alcohol dispersion of layered nano-metal oxide for multiple times to obtain an impregnated hard carbon material precursor; drying the impregnation treatments between the multiple impregnation treatments before the next impregnation treatment;
[0017] S2) subjecting the impregnated hard carbon material precursor to high temperature sintering in a protective atmosphere to induce graphitization, thereby obtaining a hard carbon material.
[0018] Preferably, the step S1) is specifically:
[0019] The hard carbon material precursor is saturatedly impregnated in an alcohol dispersion of layered nano-metal oxides, vacuum dried, and then excessively impregnated in an alcohol dispersion of layered nano-metal oxides. After drying, the impregnated hard carbon material precursor is obtained.
[0020] The present invention also provides a battery negative electrode material, comprising the hard carbon material mentioned above.
[0021] The present invention provides a hard carbon material, wherein the hard carbon material has a central portion and a surface layer; the graphitization degree of the hard carbon material gradually increases from the central portion to the surface layer. Compared with the prior art, the present invention can increase the sodium storage capacity of the hard carbon material by controlling the graphitization degree of the hard carbon material, and the local graphitization of the hard carbon material can provide more sodium storage sites, thereby improving the energy storage performance of the sodium ion battery.
[0022] The present invention provides a preparation method of a gradient graphitized hard carbon material, comprising the following steps: S1) subjecting a hard carbon material precursor to multiple impregnation treatments in an alcohol dispersion of a layered nano-metal oxide to obtain an impregnated hard carbon material precursor; performing a drying treatment between the multiple impregnation treatments and then performing the next impregnation treatment; S2) subjecting the impregnated hard carbon material precursor to high-temperature sintering in a protective atmosphere to induce graphitization to obtain a gradient graphitized hard carbon material. Compared with the prior art, the present invention achieves precise control of the graphitization gradient of hard carbon materials by using a strategy of combining layered nano-oxides and hard carbon material precursors. In this process, the layered oxides act as directing agents and have the ability to control the graphitization of hard carbon materials, so that the degree of graphitization can be gradually increased from the core to the surface. The method of the present invention is suitable for the preparation of negative electrode materials for sodium ion batteries, which can improve the sodium storage capacity, first coulomb efficiency and sample conductivity of hard carbon materials, thereby comprehensively improving the electrochemical performance of sodium ion batteries. In addition, the method can also be applied to other energy storage fields, such as lithium ion batteries, sodium-sulfur batteries, etc., which can provide new ideas and solutions for the development of energy storage technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 I is the hard carbon material obtained in Example 1 of the present invention D / I G Gradient change trend graph.
[0024] Figure 2 This is a TEM image of the hard carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Hard carbon materials are mainly composed of amorphous microporous structures and short-range ordered graphite-like phases, and the microcrystals in hard carbon are randomly oriented in the Z-axis direction. This structure is similar to the "House of Cards" model, that is, twisted graphene sheets are stacked in disorder. Because there are many nano-voids inside and the carbon layer spacing is large, it can better accommodate sodium ions for electrochemical energy storage. A low degree of graphitization corresponds to an increase in the degree of disorder inside the hard carbon material, and thus the sodium storage sites will also increase accordingly, and the capacity will increase. A high degree of graphitization corresponds to an increase in the order of the graphene plane inside the hard carbon material, the graphene plane is larger, and the π electrons can move freely in the larger graphene plane structure, so it has better conductivity.
[0027] For hard carbon materials, the difference in regulation gradients has a great impact on the usage scenarios. The greater the graphitization from the inside to the outside, the higher the conductivity and the larger the capacity, which is suitable for energy storage. The greater the graphitization from the outside to the inside, the higher the rate performance, but the lower the capacity, which is suitable for power batteries.
[0028] To solve this problem, the present invention provides a hard carbon material having a central portion and a surface layer; and the graphitization degree of the hard carbon material gradually increases from the central portion to the surface layer.
[0029] According to the present invention, the thickness ratio of the central portion to the surface layer of the hard carbon material is preferably 1:0.1 to 1.2.
[0030] The degree of graphitization of the hard carbon material provided by the present invention gradually increases from the center to the surface. Specifically, the degree of graphitization of the center is 0-20%; the degree of graphitization of the surface is 50%-80%. In the embodiment provided by the present invention, the degree of graphitization of the center of the hard carbon material is specifically 20%, 0%, 9% or 15%; the degree of graphitization of the surface of the hard carbon material is specifically 80%, 50%, 63% or 74%. And within the defined area, the degree of graphitization of the surface of the hard carbon material is a gradually increasing linear relationship. For example, if the overall degree of graphitization of the surface of the hard carbon material changes in the range of 50-80%, it means that the degree of graphitization on the outer surface is 80%, and the connection between the surface of the hard carbon material and the center of the hard carbon material is 50%; for another example, if the overall degree of graphitization of the surface of the hard carbon material changes in the range of 55-75%, it means that the degree of graphitization on the outer surface is 75%, and the connection between the surface of the hard carbon material and the center of the hard carbon material is 55%. By analogy, the meaning of the graphitization degree of the center portion being 0-20% and the specific meaning of the graphitization degree of the surface layer being 50-80% can be understood.
[0031] More specifically, the hard carbon material also includes a transition layer to smoothly transition the graphitization degree from the center to the surface. More specifically, the center and / or surface of the hard carbon material provided by the present invention is doped with a high specific volume material; the high specific volume material is a material with a higher specific volume than hard carbon that is well known to those skilled in the art, and preferably includes but is not limited to one or more of nano-silicon, nano-tin and nano-antimony; based on the weight of the hard carbon material, the doping amount of the high specific volume material is preferably 1% to 10%, more preferably 3% to 8%, and even more preferably 5%. Adding a high specific volume material to the hard carbon material can provide the material with a specific volume, while also avoiding instability caused by changes in the volume of the high specific volume material.
[0032] Or more specifically, the central portion of the hard carbon material provided by the present invention is coated with a high specific volume material to form a core-shell structure; the high specific volume material is a material with a higher specific volume than hard carbon that is well known to those skilled in the art, and preferably includes but is not limited to one or more of nano-silicon, nano-tin and nano-antimony; the mass of the high specific volume material is preferably 1% to 10% of the mass of the hard carbon material, more preferably 3% to 8%, and even more preferably 5%.
[0033] According to the present invention, the D50 particle size of the hard carbon material is preferably 2 to 20 μm; in the embodiments provided by the present invention, the D50 particle size of the hard carbon material is specifically 2 μm, 10 μm, 5 μm or 20 μm; since the hard carbon material provided by the present invention has a core and a gradient layer with different degrees of graphitization, and makes full use of the gradient design of the outer gradient layer to achieve more sodium storage points, if the particle size of the hard carbon material is smaller than the specified range, under the same secondary particle size design, if the median particle size of the primary particles is too small, the number of primary particles constituting the secondary particles of the material will increase, that is, when the secondary particles are broken during the tableting process, the outer gradient layer is the most affected, which makes it difficult to achieve the purpose of graphitization regulation; at the same time, the particle size is related to the thickness of the gradient layer, which is also the effect of graphitization regulation in statistical terms.
[0034] According to the present invention, the specific surface area of the hard carbon material is preferably 2 to 1000 m 2 / g; In some embodiments provided by the present invention, the specific surface area of the hard carbon material is specifically 2m 2 / g、1000m 2 / g, 5m 2 / g or 500m 2 / g; suitable porous hard carbon specific surface area is beneficial to improving the capacity and initial efficiency of the hard carbon composite material; especially in the present invention, by adjusting the degree of graphitization of the material, the overall specific surface area can be regulated to achieve the optimal selection.
[0035] According to the present invention, the average pore size of the hard carbon material is preferably 1 to 50 nm; in some embodiments provided by the present invention, the average pore size of the hard carbon material is specifically 1 nm, 20 nm, 2 nm or 40 nm; in the present invention, the pore size refers to the diameter of the pore (or equivalent diameter). The pore size of the hard carbon here refers to the pore size of the porous hard carbon itself when there is no material dispersed (filled) or coated in the pore structure. Hard carbon has a pore size of appropriate size, which can effectively accommodate high specific volume materials such as nano-silicon in the core, and has sufficient spatial constraint ability for high specific volume materials such as nano-silicon in the pores, thereby inhibiting the volume expansion of high specific volume materials such as nano-silicon.
[0036] According to the present invention, the pore volume of the hard carbon material is preferably 0.02 to 0.1 cm 3 / g; In some embodiments provided by the present invention, the pore volume of the hard carbon material is specifically 0.02cm 3 / g, 0.5cm 3 / g, 0.05cm 3 / g or 0.08cm 3 / g.
[0037] According to the present invention, the powder resistance of the hard carbon material is preferably 1 to 10 Ω·cm.
[0038] The present invention provides a preparation method of a gradient graphitized hard carbon material, comprising the following steps: S1) subjecting a hard carbon material precursor to multiple impregnation treatments in an alcohol dispersion of a layered nano-metal oxide to obtain an impregnated hard carbon material precursor; performing a drying treatment between the multiple impregnation treatments and then performing the next impregnation treatment; S2) subjecting the impregnated hard carbon material precursor to high-temperature sintering in a protective atmosphere to induce graphitization to obtain a gradient graphitized hard carbon material.
[0039] The present invention controls the distribution of layered oxides in hard carbon materials and induces local graphitization, thereby achieving a layered structure with a core that is difficult to graphitize and a gradually increasing degree of graphitization from the center to the surface. Such structural regulation helps to optimize the performance and application of hard carbon materials.
[0040] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0041] According to the present invention, the hard carbon material precursor is preferably one or more of a biomass precursor, cellulose, hemicellulose, lignin and a phenolic resin.
[0042] According to the present invention, the nano-metal oxide in the raw material is preferably one or more of layered nano-aluminum oxide, nano-boehmite, layered nano-zirconium oxide, layered nano-magnesium oxide, layered nano-manganese oxide, layered nano-nickel oxide, layered nano-cobalt oxide, layered nano-zinc oxide, layered nano-copper oxide and layered nano-iron oxide.
[0043] According to the present invention, the alcohol dispersion of layered nano metal oxide is preferably an ethanol dispersion of layered nano metal oxide; the mass concentration of layered nano metal oxide in the alcohol dispersion of layered nano metal oxide used in the present invention is preferably 0.1% to 10%, more preferably 1% to 10%, more preferably 1% to 5%, more preferably 1% to 3%, and most preferably 2% to 3%; the alcohol dispersion of layered nano metal oxide is preferably prepared according to the following method: mixing layered nano metal oxide with an alcohol solvent and stirring in a high-speed degassing mixer to obtain an alcohol dispersion of layered nano metal oxide; the alcohol solvent can be an alcohol solvent well known to those skilled in the art, without special restrictions, and is preferably ethanol in the present invention.
[0044] The hard carbon material precursor is impregnated multiple times in an alcohol dispersion of layered nano-metal oxides to obtain an impregnated hard carbon material precursor; wherein the mass ratio of the hard carbon material precursor to the alcohol dispersion of the layered nano-metal oxides is preferably (0.1-1):1; the number of multiple impregnation treatments is preferably 2-4 times, more preferably 2-3 times; the number of impregnation treatments will affect the gradient range of the surface graphitization degree of the hard carbon material, so the number of impregnation treatments can be adjusted according to the designed graphitization degree to achieve the set effect; further, the multiple impregnation treatments in the present invention preferably include saturated impregnation treatment and excessive impregnation treatment, and more preferably, saturated impregnation treatment is first performed and then The method comprises the following steps: performing an over-impregnation treatment; performing a drying treatment between multiple impregnation treatments and then performing the next impregnation treatment, preferably performing a drying treatment and then pulverizing before performing the next impregnation treatment; the drying treatment between multiple impregnation treatments is preferably a vacuum drying treatment to quickly solidify the sample; the drying after multiple impregnation treatments is preferably a normal drying treatment to form a gradient distribution of the layered nano-metal oxide in the hard carbon material precursor; in the present invention, the specific steps are as follows: performing a saturated impregnation treatment on the hard carbon material precursor in an alcohol dispersion of the layered nano-metal oxide, vacuum drying, performing an over-impregnation treatment in an alcohol dispersion of the layered nano-metal oxide, and drying to obtain a hard carbon material after the impregnation treatment. Precursor; wherein, during the saturated impregnation treatment, the mass ratio of the hard carbon material precursor to the alcohol dispersion of the layered nano-metal oxide is preferably (0.5-1):1, more preferably (0.6-1):1, more preferably (0.7-0.9):1, and most preferably 0.8:1; the hard carbon material precursor is allowed to fully absorb the alcohol dispersion of the layered nano-metal oxide through the saturated impregnation treatment; the vacuum drying temperature is preferably 100°C-140°C, more preferably 110°C-130°C, and more preferably 120°C; the vacuum drying time is preferably 4-8h, more preferably 5-7h, and more preferably 6h; after vacuum drying, it is preferably crushed and then subjected to excessive impregnation treatment; During the excessive impregnation treatment, the mass ratio of the hard carbon material precursor to the alcohol dispersion of the layered nano-metal oxide is preferably (0.1-0.5):1, more preferably (0.1-0.4):1, more preferably (0.2-0.4):1, more preferably (0.2-0.3):1, and most preferably (0.25-0.3):1; the time of the excessive impregnation treatment is preferably 0.5-6h, more preferably 1-4h, and more preferably 2-3h; the drying temperature is preferably 60℃-90℃, more preferably 70℃-90℃, more preferably 75℃-85℃, and most preferably 80℃; the drying time is preferably 8-16h, more preferably 8-12h.
[0045] The hard carbon material precursor after impregnation treatment is subjected to high-temperature sintering in a protective atmosphere to induce graphitization to obtain a gradient graphitized hard carbon material; wherein the protective atmosphere used can be any protective atmosphere familiar to those skilled in the art, without special restrictions, and is preferably nitrogen and / or argon in the present invention; the flow rate of the protective atmosphere is preferably 100-500 mL / min, more preferably 200-400 mL / min, and more preferably 300 mL / min; the temperature of high-temperature sintering is preferably 800°C-1600°C, more preferably 800°C-1400°C; in some embodiments provided by the present invention, the temperature of high-temperature sintering is specifically 1600°C, 800°C, 1400°C or 1000°C; the time of high-temperature sintering is preferably 2-8h; in some embodiments provided by the present invention, the time of high-temperature sintering is specifically 8h, 2h, 6h or 4h; the heating rate of high-temperature sintering is preferably 0.5-10°C / min, more preferably 0.5-5°C / min. When layered oxides are introduced into hard carbon material precursors, their structures can serve as templates to induce the graphitization process of hard carbon materials. During the graphitization process, carbon atoms tend to arrange themselves into structures similar to layered oxides and interact with them to form layered graphite-like structures. The lattice structure of layered oxides provides a reference framework for carbon atoms, making it easier for them to form similar layered structures. Due to the gradient distribution of oxides in hard carbon materials, gradient regulation of the graphitization process of hard carbon materials is achieved.
[0046] Since the layered oxide contains metal ions, in order to remove metal impurities, it is preferably immersed in an acid solution after high-temperature sintering to induce graphitization to obtain a hard carbon material; the acid solution used in the present invention is an acid solution well known to those skilled in the art, including but not limited to nitric acid solution; the concentration of the acid solution is preferably 0.3-1.5 mol / L, more preferably 0.5-1 mol / L; the immersion treatment time is preferably 20-60h, more preferably 30-55h, more preferably 40-50h, and most preferably 48h.
[0047] When a high specific volume material is doped and distributed in the center of the hard carbon material, the hard carbon material preferably first mixes part of the hard carbon precursor with the high specific volume material, then wraps the rest of the hard carbon precursor on the outside, and then performs multiple immersion treatments in an alcohol dispersion of layered nanometal oxides to obtain an impregnated hard carbon material precursor; the remaining steps are the same as described above.
[0048] When the center and / or surface of the hard carbon material are doped and distributed with a high specific volume material, in the hard carbon material process, the alcohol dispersion of the layered nano metal oxide preferably contains the high specific volume material, and the hard carbon material precursor is impregnated multiple times in the alcohol dispersion of the layered nano metal oxide containing the high specific volume material to obtain an impregnated intermediate, and the remaining steps are the same as described above. Introducing the high specific volume material during the impregnation process can make the high specific volume material such as nano silicon more dispersedly embedded in the carbon to prevent the volume from expanding and shrinking significantly due to the local enrichment of the high specific volume material.
[0049] When the center of the hard carbon material is coated with a high specific volume material to form a core-shell structure, the hard carbon material is preferably prepared according to the following steps: A1) wrapping a hard carbon material precursor around the high specific volume material to obtain an intermediate; A2) impregnating the intermediate in an alcohol dispersion of layered nanometal oxides for multiple times to obtain an impregnated intermediate; drying the intermediate between the multiple impregnation treatments before the next impregnation treatment; A3) sintering the impregnated intermediate at high temperature in a protective atmosphere to induce graphitization to obtain a hard carbon material.
[0050] The present invention realizes precise control of the graphitization gradient of hard carbon materials by using a strategy of combining layered nano-oxides and hard carbon material precursors. In this process, the layered oxides serve as directing agents and have the ability to control the graphitization of hard carbon materials, so that the degree of graphitization is gradually increased from the core to the surface. The method of the present invention is suitable for the preparation of negative electrode materials for sodium ion batteries, and can improve the sodium storage capacity, first coulomb efficiency and sample conductivity of hard carbon materials, thereby comprehensively improving the electrochemical performance of sodium ion batteries. In addition, the method can also be applied to other energy storage fields, such as lithium ion batteries, sodium-sulfur batteries, etc., and can provide new ideas and solutions for the development of energy storage technology.
[0051] The present invention also provides a battery negative electrode material, comprising the above-mentioned gradient graphitized hard carbon material.
[0052] Further preferably, the battery negative electrode material is a core-shell structure; the core of the battery negative electrode material is a silicon material, preferably crystalline silicon; the silicon material is used as the storage layer; the shell layer of the battery negative electrode material is the above-mentioned gradient graphitized hard carbon material.
[0053] According to the present invention, the battery negative electrode material includes a core layer, an intermediate layer and a shell layer; the core layer is a silicon material, preferably crystalline silicon; the intermediate layer is a hard carbon material with a low degree of graphitization; and the shell layer is a highly graphitized hard carbon material.
[0054] The method of the present invention realizes the precise control of the graphitization gradient of hard carbon materials and has the following beneficial effects:
[0055] 1) Improve sodium storage capacity: By controlling the degree of graphitization of hard carbon materials, their sodium storage capacity can be increased. The partial graphitization of hard carbon materials can provide more sodium storage sites, thereby improving the energy storage performance of sodium-ion batteries.
[0056] 2) Gradient control: This method can achieve a layered structure with a core that is difficult to graphitize and a gradually increasing degree of graphitization from the center to the surface. This gradient-controlled structure can better meet the needs of different applications while taking into account the stability and performance optimization of the material.
[0057] 3) Improved electrochemical properties: The electrochemical properties of hard carbon materials can be optimized by introducing layered oxides as directing agents. The lattice structure of layered oxides provides a reference framework for hard carbon materials, helps to form similar layered graphite structures, and improves electrical conductivity and ion transport efficiency.
[0058] 4) Simple preparation and low cost: This method uses conventional impregnation and sintering processes, and the preparation process is simple and easy to operate. The required materials and equipment are easy to obtain, and no complicated preparation conditions are required, thereby reducing the preparation cost.
[0059] In order to further illustrate the present invention, the present invention provides a gradient graphitized hard carbon material, a preparation method thereof and applications are described in detail below in conjunction with embodiments.
[0060] The reagents used in the following examples are all commercially available; the soft water stone used in the examples and comparative examples is Shandong Yulong New Materials Co., Ltd., YL-0016; the cellulose is McLean, C804602-50g; the thickener carboxymethyl cellulose is Shenzhen Youyan Technology Co., Ltd., CMC-2200; the binder styrene butadiene rubber is JSR Japan / carboxylated styrene butadiene rubber emulsion synthetic rubber TRD104A; the glass fiber separator is Shenzhen Youyan Technology Co., Ltd., GF / D 1823-047; nano silicon is 50nm nano silicon sold by Shenzhen Youyan Technology Co., Ltd.; nano alumina is nano alumina for lithium batteries sold by Shenzhen Youyan Technology Co., Ltd.; the electrochemical properties of the hard carbon materials in the examples are measured according to the standard GB / T24533-2009, and the main evaluation factors include reversible specific capacity, first coulomb efficiency, and cycle retention rate.
[0061] Example 1
[0062] 1.1 Weigh 0.2 g of γ-AlOOH and mix with 9.8 g of ethanol. Put the mixture into a high-speed degassing mixer and stir to prepare a layered nano-alumina ethanol dispersion with a mass concentration of 2%.
[0063] 1.2 2g of cellulose (McLean, C804602-50g) was soaked in 2.5g of dispersion for saturation impregnation. After the cellulose fully absorbed the dispersion, it was transferred to a vacuum oven and dried at 120°C for 6h. After drying, the sample was crushed and then immersed in 7.5g of dispersion for excessive impregnation. After immersion for 2h, it was transferred to a conventional oven at 80°C and dried overnight to prepare a hard carbon material precursor with a gradient distribution of aluminum oxide.
[0064] 1.3 Place the hard carbon material precursor with alumina gradient distribution into a tubular furnace, start the inert gas protection device, introduce argon gas to provide protection, the argon flow rate is 300 mL / min, and then start the high-temperature sintering process, raising the temperature to 1600°C at 2°C / min, sintering for 8 hours to obtain an intermediate.
[0065] 1.4 The intermediate obtained in the previous step was mixed with 100 mL of 0.5 M nitric acid solution, and then filtered and dried after standing for 48 hours to obtain a hard carbon material. The purpose of this step is to remove aluminum and various trace metal element impurities that may exist in the hard carbon material.
[0066] The hard carbon material obtained in Example 1 was tested and its specific surface area was found to be 2 m 2 / g, D50 = 2 microns, average pore diameter 1 nm, pore volume 0.02 cm 3 / g.
[0067] Currently, for graphite materials, the degree of graphitization is measured according to the standard QJ 2507 93, using X-ray diffraction method for determination, but this method cannot effectively determine the degree of graphitization of a local area of the material. In order to deeply test the degree of local graphitization of hard carbon materials, the present invention uses argon ions with an energy of 500eV to 5keV to perform deep sputtering on the material, the beam spot diameter of the ion beam is 10mm, and the sputtering rate range is 10nm / min. The etching depth of the material can be controlled by sputtering the material intermittently, and the degree of graphitization of the material at different depths can be evaluated by combining Raman spectroscopy, and I D / I G The ratio is quantitatively characterized. Figure 1 Material Center I D / I G The ratio is about 1.2 (i.e. the graphitization degree is 20%), and the surface shell of the material I D / I G The ratio is about 0.6 (corresponding to the original graphitization degree of 80%). At the same time, according to the formula: La = (a + b·λ) / (I D / I G), where La is the average size of graphite crystals along the a-axis, that is, the size of the graphene plane (which can be understood as the smallest plane structure of carbon materials, and carbon materials are composed of many graphene planes of different sizes). It can be seen that the ratio of the size of the graphene plane on the surface of the hard carbon material and the center of the bulk phase is La 表层 / La 核心 =2. According to the general knowledge of the prior art on the Raman defects of natural graphite, D / I G It is about 0.4, which can be defined as 100% graphitization. In this application, the graphitization degree is related to I D / I G The corresponding relationship can be roughly described as follows: D / I G =1.4, the degree of graphitization is 0%; I D / I G =1.2, the degree of graphitization is 20%; I D / I G =1.0, the degree of graphitization is 40%; I D / I G =0.8, the degree of graphitization is 60%; I D / I G =0.6, the degree of graphitization is 80%; I D / I G =0.4, the graphitization degree is 100%. Since the present invention achieves uniformly modified graphitization degree through solution wettability and infiltration time, a relatively smooth graphitization degree change curve can be obtained, so the range interval can be regarded as a uniform change in the region.
[0068] Transmission electron microscopy (TEM): TEM is a high-resolution microscopy technique that can be used to observe and analyze the microstructure of materials. By observing the high-resolution image of the hard carbon material obtained in Example 1 through TEM, it is possible to directly observe the local highly graphitized area formed in the surface shell, such as Figure 2 As shown. Figure 2 It can be seen that the locally graphitized areas present a graphite-like structure in the TEM images, showing a higher layered structure.
[0069] The hard carbon material provided in Example 1 is assembled into a negative electrode sheet and a sodium ion battery according to the following method:
[0070] Negative electrode: According to the mass ratio of 95:2:0.5:2.5, the hard carbon material, conductive agent (conductive carbon black, Super P), thickener (carboxymethyl cellulose, CMC), binder (styrene butadiene rubber, SBR: JSR Japan / carboxyl styrene butadiene rubber latex synthetic rubber TRD104A) prepared above were placed in deionized water and mixed evenly to prepare negative electrode slurry, and the negative electrode slurry was coated on the surface of the current collector copper foil. The electrode sheet thickness was 40 μm and the surface density was 5 mg / cm 2 After drying-rolling-secondary drying process, the negative electrode sheet is obtained.
[0071] The counter electrode is a sodium metal sheet with stable characteristics.
[0072] Electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (DEC) were mixed in a volume ratio of 1:1, and NaPF6 was added to form an electrolyte, the concentration of NaPF6 was 1.2 mol / L;
[0073] Diaphragm: Fiberglass.
[0074] Sodium ion battery assembly: Sodium ion batteries are assembled in an inert atmosphere glove box according to the structure of negative electrode sheet-diaphragm-electrolyte-sodium sheet.
[0075] Related performance test analysis:
[0076] The electrochemical performance of each sodium ion battery assembled in the above sodium ion battery embodiment and comparative example was tested, and the test conditions were: the assembled button battery was charged and discharged at room temperature, and the charge and discharge voltage range was 0V-1.5V.
[0077] When the hard carbon material obtained in Example 1 is used as the negative electrode material of a sodium ion battery, the reversible specific capacity of the charge is 350 mAh / g, the initial coulombic efficiency is 92.5%, and the retention rate of 500 cycles at a charge and discharge rate of 0.2C is 99%. At the same time, the electrode resistivity of the material is 0.6 Ω·cm and the powder resistance is 0.2 Ω·cm.
[0078] Example 2
[0079] 2.1 Weigh 0.2 g of γ-AlOOH and mix with 9.8 g of ethanol. Put the mixture into a high-speed degassing mixer and stir to prepare a layered nano-alumina ethanol dispersion with a mass concentration of 2%.
[0080] 2.2 2g of cellulose (McLean, C804602-50g) was soaked in 2.5g of dispersion for saturation impregnation. After the cellulose fully absorbed the dispersion, it was transferred to a vacuum oven and dried at 120°C for 6h. After drying, the sample was crushed and then immersed in 7.5g of dispersion for excessive impregnation. After immersion for 2h, it was transferred to a conventional oven at 80°C and dried overnight to prepare a hard carbon material precursor with a gradient distribution of aluminum oxide.
[0081] 2.3 Place the hard carbon material precursor with alumina gradient distribution into a tubular furnace, start the inert gas protection device, introduce argon to provide protection, the argon flow rate is 300 mL / min, and then start the high-temperature sintering process, raising the temperature to 800°C at 0.5°C / min, sinter for 2 hours to obtain an intermediate.
[0082] 2.4 Mix the intermediate obtained in the previous step with 100 mL of 0.5 M nitric acid solution, let it stand for 48 hours, and then filter and dry it to obtain a hard carbon material.
[0083] The hard carbon material obtained in Example 2 was tested and its specific surface area was found to be 1000 m 2 / g, D50 = 10 microns, average pore diameter 20 nm, pore volume 0.5 cm 3 / g, the graphitization degree of the material center is 0%, and the graphitization degree of the material surface shell is 50%.
[0084] According to the method of Example 1, the hard carbon material obtained in Example 2 was tested as the negative electrode material of a sodium ion battery, and the reversible specific capacity was 460 mAh / g, the initial coulombic efficiency was 80.1%, and the retention rate of 500 cycles at a charge and discharge rate of 0.2C was 97%. At the same time, the electrode resistivity of the material was 100 Ω·cm, and the powder resistance was 10 Ω·cm.
[0085] Example 3
[0086] 3.1 Weigh 0.2 g of γ-AlOOH and mix with 9.8 g of ethanol. Place the mixture in a high-speed degassing mixer and stir to prepare a layered nano-alumina ethanol dispersion with a mass concentration of 2%.
[0087] 3.2 2g of cellulose was soaked in 2.5g of dispersion for saturation impregnation. After the cellulose fully absorbed the dispersion, it was transferred to a vacuum oven and dried at 120°C for 6h. After drying, the sample was crushed and then immersed in 7.5g of dispersion for excessive impregnation. After immersion for 2h, it was transferred to an ordinary oven at 80°C and dried overnight to prepare a hard carbon material precursor with a gradient distribution of aluminum oxide.
[0088] 3.3 Place the hard carbon material precursor with alumina gradient distribution into a tubular furnace, start the inert gas protection device, introduce argon to provide protection, the argon flow rate is 300mL / min, and then start the high-temperature sintering process, raising the temperature to 1400℃ at 5℃ / min, sintering for 6h, and the intermediate.
[0089] 3.4 Mix the intermediate obtained in the previous step with 100 mL of 0.5 M nitric acid solution, let it stand for 48 hours, and then filter and dry it to obtain a hard carbon material.
[0090] The hard carbon material obtained in Example 3 was tested and its specific surface area was found to be 5m 2 / g, D50 = 5 microns, average pore diameter 2nm, pore volume 0.05cm 3 / g, the graphitization degree of the material center is 9%, and the graphitization degree of the material surface shell is 63%.
[0091] According to the method of Example 1, when the hard carbon material obtained in Example 3 is used as the negative electrode material of a sodium ion battery, the reversible specific capacity of the hard carbon material is 345 mAh / g and the first coulombic efficiency is 90.1%. At the same time, the electrode resistivity of the material is 0.9 Ω·cm and the powder resistance is 1 Ω·cm.
[0092] Example 4
[0093] 4.1 Weigh 0.5 g of layered nano manganese oxide and 9.5 g of ethanol and mix them. Put the mixture into a high-speed degassing mixer and stir to prepare a layered nano aluminum oxide ethanol dispersion with a mass concentration of 5%.
[0094] 4.2 Soak 2g of coconut shell powder in 2.5g of dispersion for saturation impregnation. After the coconut shell powder fully absorbs the dispersion, transfer it to a vacuum oven and dry it at 120°C for 6h. After drying, the sample is crushed and then impregnated in the second stage, that is, it is immersed in 7.5g of dispersion for excessive impregnation. After impregnation for 2h, it is transferred to an ordinary oven at 80°C and dried overnight to prepare a hard carbon material precursor with a gradient distribution of manganese oxide.
[0095] 4.3 Place the hard carbon material precursor with a gradient distribution of manganese oxide into a tubular furnace, start the inert gas protection device, introduce argon gas to provide protection, the argon flow rate is 300 mL / min, and then start the high-temperature sintering process, raising the temperature to 1000°C at 2°C / min, sintering for 4 hours to obtain an intermediate.
[0096] 4.4 Mix the intermediate obtained in the previous step with 100 mL of 0.5 M nitric acid solution, let it stand for 48 hours, and then filter and dry it to obtain a hard carbon material.
[0097] The hard carbon material obtained in Example 4 was tested and its specific surface area was found to be 500 m 2 / g, D50 = 20 microns, average pore diameter 40 nm, pore volume 0.08 cm 3 / g, the graphitization degree of the material center is 15%, and the graphitization degree of the material surface shell is 74%.
[0098] When the hard carbon material obtained in Example 4 is tested as a negative electrode material for a sodium ion battery according to the method of Example 1, the reversible specific capacity is 355 mAh / g and the first coulombic efficiency is 91.3%. At the same time, the electrode resistivity of the material is 0.8 Ω·cm and the powder resistance is 1.2 Ω·cm.
[0099] Example 5
[0100] The sample was prepared according to the method of Example 1, except that during the over-impregnation, the mass ratio of the sample to the dispersion was 0.1:1.
[0101] Example 6
[0102] The sample was prepared according to the method of Example 1, except that during the over-impregnation, the mass ratio of the sample to the dispersion was 0.5:1.
[0103] Example 7
[0104] The method of Example 1 was followed, except that the concentration of the layered nano-alumina in the dispersion was 0.1%.
[0105] Example 8
[0106] The method of Example 1 was followed, except that the concentration of the layered nano-alumina in the dispersion was 10%.
[0107] Example 9
[0108] According to the method of Example 1, the nano-silicon is mixed with the impregnation liquid and then introduced into the carbon source together with the impregnation liquid. The doping amount of the nano-silicon is equivalent to 3% of the mass of the hard carbon material.
[0109] Example 10
[0110] According to the method of Example 1, the nano-silicon is mixed with the impregnation liquid and then introduced into the carbon source together with the impregnation liquid. The doping amount of the nano-silicon is equivalent to 5% of the mass of the hard carbon material.
[0111] Comparative Example 1
[0112] 2 g of cellulose was placed in a tubular furnace, and the inert gas protection device was started. Argon was introduced to provide protection at a flow rate of 300 mL / min. Then the high-temperature sintering process was started, and the temperature was raised to 1600°C at a rate of 2°C / min. The hard carbon material was sintered for 8 hours. The graphitization degree of the material center and the surface shell was 0%.
[0113] The hard carbon negative electrode material obtained in Comparative Example 1, when used as a negative electrode material for a sodium ion battery, has a reversible specific capacity of 240 mAh / g, an initial coulombic efficiency of 74.9%, and a 500 cycle retention rate of only 80% at a charge and discharge rate of 0.2C. At the same time, the electrode sheet resistivity of the material is 600 Ω·cm and the powder resistance is 20 Ω·cm.
[0114] Comparative Example 2
[0115] The hard carbon material was prepared according to the method of Example 1, except that the soft water stone (γ-AlOOH) was replaced by nano-alumina, and the performance of the hard carbon material was tested.
[0116] The performance test results of the hard carbon materials obtained in Examples 1 to 10 and Comparative Examples 1 and 2 are shown in Table 1.
[0117] Table 1 Hard carbon material performance test results
[0118]
[0119] It can be seen from Table 1 that a high sintering temperature helps to increase the specific surface area of the hard carbon material, thereby helping to improve the bulk conductivity and stability of the hard carbon material.
[0120] Specifically, in Example 1, the graphitization degree of the surface layer is adjusted to be close to graphite, and the internal graphitization degree is controlled within a reasonable range, thereby maintaining good first efficiency and rate performance, and having extremely low powder resistivity. However, due to the slightly higher degree of graphitization of the inner layer, its first charging capacity is affected; but the overall performance is well controlled.
[0121] In general, the first effect decreases with the increase of specific surface area. However, in the present invention, the degree of graphitization with gradient changes in different regions is regulated, especially when there is a high degree of graphitization in the surface layer, defects can be effectively shielded to form closed pores, while a hard carbon structure still exists inside. For example, compared with Examples 3 and 7, Example 4 has a much higher specific surface area than Examples 3 and 7. However, due to the high degree of graphitization in the surface region, a good first effect can still be achieved. At the same time, due to the large difference in graphitization degree with the interior, a good hard carbon structure is maintained inside, and a higher sodium storage point can be provided, with excellent first capacity performance. In addition, when La surface / La core is close to 2, it can be regulated to a better overall powder resistivity, which is also a particularly critical parameter of the present invention. The inner and outer layers are regulated simultaneously to achieve a better overall performance.
[0122] In summary, the method of the present invention can achieve precise control of the graphitization gradient of hard carbon materials, increase sodium storage capacity, improve electrochemical performance, and has the advantages of simple preparation and low cost. This technology has important application prospects and practical value in energy storage fields such as sodium ion batteries.
Claims
1. A hard carbon material, characterized in that: The hard carbon material has a central portion and a surface layer; the graphitization degree of the hard carbon material gradually increases from the central portion to the surface layer; The thickness ratio of the central part to the surface layer is 1:0.1-1.2; The graphitization degree of the central portion ranges from 0% to 20%; the graphitization degree of the surface layer ranges from 50% to 80%; The method for preparing the hard carbon material comprises the following steps: S1) impregnating the hard carbon material precursor in an alcohol dispersion of layered nano-metal oxide for multiple times to obtain an impregnated hard carbon material precursor; drying the impregnation treatments before the next impregnation treatment; S2) sintering the impregnated hard carbon material precursor in a protective atmosphere at a high temperature to induce graphitization, thereby obtaining a hard carbon material; The hard carbon material precursor is selected from one or more of cellulose, hemicellulose, lignin and phenolic resin.
2. The hard carbon material according to claim 1, characterized in that The central part and / or the surface layer are doped and dispersed with high specific volume materials; the high specific volume materials are one or more of nano silicon, nano tin and nano antimony.
3. The hard carbon material according to claim 1, characterized in that The central portion is coated with a high specific volume material to form a core-shell structure, and the high specific volume material is one or more of nano-silicon, nano-tin and nano-antimony.
4. The hard carbon material according to claim 1, characterized in that The D50 particle size of the hard carbon material is 2-20 μm; And / or, the specific surface area of the hard carbon material is 2 to 1000 m 2 / g; And / or, the average pore size of the hard carbon material is 1 to 50 nm; And / or, the pore volume of the hard carbon material is 0.02-0.1 cm 3 / g.
5. The hard carbon material according to claim 4, characterized in that The powder resistance of the hard carbon material is 1-10Ω·cm.
6. The hard carbon material according to claim 1, characterized in that The step S1) is specifically as follows: The hard carbon material precursor is saturatedly impregnated in an alcohol dispersion of layered nano-metal oxides, vacuum dried, and then excessively impregnated in an alcohol dispersion of layered nano-metal oxides. After drying, the impregnated hard carbon material precursor is obtained.
7. A battery negative electrode material, characterized in that: The hard carbon material comprises the hard carbon material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method for graphite negative electrode of lithium ion battery
CN102983307A
Hard carbon material, preparation method thereof and application of hard carbon material in sodium-ion battery
CN115124025A